MEK inhibitors for neurofibromatosis type 1 manifestations: Clinical evidence and consensus. Issue 11 (5th July 2022) - de Blank, Peter M K; Gross, Andrea M; Akshintala, Srivandana; Blakeley, Jaishri O; Bollag, Gideon; Cannon, Ashley; Dombi, Eva; Fangusaro, Jason; Gelb, Bruce D; Hargrave, Darren; Kim, AeRang; Klesse, Laura J; et al.
Abstract: The wide variety of clinical manifestations of the genetic syndrome neurofibromatosis type 1 (NF1) are driven by overactivation of the RAS pathway. Mitogen-activated protein kinase kinase inhibitors (MEKi) block downstream targets of RAS. The recent regulatory approvals of the MEKi selumetinib for inoperable symptomatic plexiform neurofibromas in children with NF1 have made it the first medical therapy approved for this indication in the United States, the European Union, and elsewhere. Several recently published and ongoing clinical trials have demonstrated that MEKi may have potential benefits for a variety of other NF1 manifestations, and there is broad interest in the field regarding the appropriate clinical use of these agents. In this review, we present the current evidence regarding the use of existing MEKi for a variety of NF1-related manifestations, including tumor (neurofibromas, malignant peripheral nerve sheath tumors, low-grade glioma, and juvenile myelomonocytic leukemia) and non-tumor (bone, pain, and neurocognitive) manifestations. We discuss the potential utility of MEKi in related genetic conditions characterized by overactivation of the RAS pathway (RASopathies). In addition, we review practical treatment considerations for the use of MEKi as well as provide consensus recommendations regarding their clinical use from a panel of experts.